FORMULATION AND EFFECTIVITY TEST OF DEODORANT FROM ACTIVATED CHARCOAL OF PALM SHELL AS EXCESSIVE SWEAT ADSORBENT ON BODY - UCE LESTARI; FAIZAR FARID; AHMAD FUDHOLI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to know the physically stable deodorant preparations during storage and to obtain the preparations. Methods: The evaluation of the physical properties of deodorant include: Organoleptic test, homogeneity, pH measurement, viscosity, flow properties, drying time, moisture content, flow time, density, cycling test, hedonic test, irritation test, and effectivity test of sweat adsorption. Activated charcoal used by the formulation of deodorant powder and roll on each with a concentration of 15%. Results: The physicochemical evaluation was obtained. Descriptively produced data stated that deodorant powder is more physically stable that deodorant roll-on which has separated during storage. Conclusion: For the effectivity of sweat adsorption, deodorant powder is more effective than deodorant roll-on.